2009
DOI: 10.4314/jasr.v6i2.47018
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Abattoir records for Imo state, Nigeria from 1995 - 1999 IV: Incidence of Mastitis Amongs cattle, sheep and goats

Abstract: A five-year data (1995)(1996)(1997)(1998)(1999) on mastitis among slaughtered cattle, sheep and goats collected from the Federal Livestock Department (FLD), Imo State zonal office, was analysed to determine the prevalence of the condition among such animals in Imo State. Of the 8615 female animals handled at veterinary approved slaughter points during the period, 6230 (72.8%), 497(5.8%) and 1848(21.4%) were cows, ewes and does respectively. Mastitis was recorded among 405 (6.6%) of the cows, 77(15.5%) of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 2 publications
1
9
0
Order By: Relevance
“…The livestock population in Bangladesh is currently estimated to comprise 26.828 million cattle, 0.544 million buffalo, 16.242 million goat and 1.221 million sheep [2] which plays an important role in the rural economy [3]. Fascioliasis, caused by Fasciola hepatica and F. gigantica, is one of the most prevalent helminthes infections of ruminants in different parts of the world inducing significant morbidity and mortality [21] as well as lower production of ruminants [20]. This group of liver fluke (Fasciola sp.)…”
Section: Introductionmentioning
confidence: 99%
“…The livestock population in Bangladesh is currently estimated to comprise 26.828 million cattle, 0.544 million buffalo, 16.242 million goat and 1.221 million sheep [2] which plays an important role in the rural economy [3]. Fascioliasis, caused by Fasciola hepatica and F. gigantica, is one of the most prevalent helminthes infections of ruminants in different parts of the world inducing significant morbidity and mortality [21] as well as lower production of ruminants [20]. This group of liver fluke (Fasciola sp.)…”
Section: Introductionmentioning
confidence: 99%
“…Fascioliasis has been implicated as the cause of morbidity and mortality in the production of ruminants (Okoli 2001). Fascioliasis is a trematode borne parasitic disease that infects the liver of large ruminants widely prevalent throughout the world.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no relationship between unilateral infection and the half (right or left) of the gland affected (Ameh et al, 1993;Ameh and Tsari, 1999). Similarly, Okoli et al (2006) reported a prevalence of 19% out of 1848 does presented for slaughter at an abattoir in Imo state, Nigeria. Necrosis of the mammary gland with gangrene formation was reported in a goat with coliform mastitis (Ameh et al, 1994).…”
Section: Introductionmentioning
confidence: 94%